The role of parental characteristics, home language use, and schooling in children's Mandarin heritage language development in Canada - Daskalaki, Evangelia; Soto-Corominas, Adriana; Xia, Vera Yunxiao; Paradis, Johanne (Frontiers in Language Sciences, 2024)
This study on child HL (heritage language) speakers of Mandarin examines the associations between parental characteristics (attitudes and proficiency), children's HL use (at home and through schooling), and children's HL outcomes (in vocabulary and simple syntax). Forty-seven Mandarin-English bilingual children of Chinese heritage (mean age: 10.5; age range: 6.8-16.2) residing in Western Canada participated in the study. All children were second-generation immigrants, and received one of three types of schooling. There were 11 children who attended English-only schools (English school group), 21 that attended English-only schools but also afterschool heritage Mandarin classes (Heritage school group), and 15 that attended English-Mandarin bilingual schools (Bilingual school). The children were administered two tasks: a picture-naming task targeting Mandarin vocabulary (LITMUS-CLT) and an experimental elicitation task targeting Mandarin wh-interrogative sentences (an early-acquired structure). Parents were administered a questionnaire about home language environment, attitudes towards Mandarin transmission, and their children's schooling choices. Results showed that positive parental attitudes and lower parental proficiency in English were associated with more Mandarin use at home. More Mandarin use at home, in turn, was associated with larger vocabularies and more accurate production of interrogatives. By contrast, school type was only associated with vocabulary and not syntax: the Bilingual school group had larger vocabularies than the English school group. Overall, these results show how parental characteristics may influence input factors, which in turn may differentially affect the acquisition of vocabulary versus early-acquired syntactic structures.